Financiamento, gasto e regionalização: uma análise da região de saúde metropolitana da Baixada Santista (2006 a 2012) - Lara, Natalia Carolina Cairo (2013)
The regionalization of the Unified Health System (SUS), is one of the guidelines that should guide the organization of the NHS, according to the 1988 Constitution. The process of decentralization of health is a movement that started its structure over the 80 and defined the Constitution and the subsequent constitutional legislation (Law 8080, Law 8142, rules, regulations and decrees regulated). Since its construction, we observe policies of decentralization and regionalization of SUS, which start with NOBs, passing through NOAS, Covenant Health, and recently the Organisational Agreement and Public Health Action (COAP). To discuss and understand the process of regionalization of SUS, was studied the Metropolitan Health Region of Santos in the light of its financing capacity and analysis of your spending. Thus, we look at how this region is organized in a financially effective regional management